Characteristics of quetiapine and 7-hydroxyquetiapine in hair roots and blood after a single dose of quetiapine. (April 2020) - Yan, Hui; Ji, Jiao-jiao; Xiang, Ping; Shen, Min
Highlights: Drugs can be detected in hair root in 15 min after administration. Quetiapine level in hair roots were positively correlated with doses within 24 h. Hair root analysis may be a good choice to detect acute poisoning. Abstract: This study investigated the kinetics of quetiapine and its metabolite 7-hydroxyquetiapine in guinea pig blood and hair roots during the whole time course of absorption and elimination after intragastric administration of three dosages (25 mg/kg, 50 mg/kg, 100 mg/kg). The mean maximum concentration (Cmax ) values of quetiapine in the blood of the low-, medium- and high-dose groups were 334.4, 849.0, and 2751.1 ng/mL, respectively, and those of 7-hydroxyquetiapine were 75.6, 175.5, and 173.7 ng/mL, respectively. The corresponding mean Cmax values of quetiapine in hair roots were 2.0, 5.9, and 14.7 ng/mg, and those of 7-hydroxyquetiapine were 1.0, 1.8, and 6.4 ng/mg. The mean half-lives of quetiapine at the three dosages in blood were 3.8 h, 5.0 h, and 6.0 h, and those in hair roots were 48.2 h, 41.5 h, and 162.3 h; for 7-hydroxyquetiapine, the values were 2.9 h, 4.1 h, and 4.2 h in blood and 77.1 h, 103.6 h, and 385.9 h in hair roots. The levels of quetiapine in blood and hair roots were higher than those of 7-hydroxyquetiapine, and there were significant positive correlations (p < 0.05) between the concentrations of quetiapine and 7-hydroxyquetiapine in hair roots and the respective doses within 24 h and 48 h. Quetiapine and 7-hydroxyquetiapine could still be detected in some guinea pigs even after 28 days, which means that drugs remain in the hair roots longer than in the blood. This finding shows that hair roots could be a good alternative or supplemental matrix to common biological samples such as blood and urine, as hair roots substantially extend the detection window from days to months. Moreover, quetiapine and 7-hydroxyquetiapine were detected within 15 min after administration in hair roots, which also suggests that the drug enters the hair roots quickly. Therefore, hair root analysis may be a good choice to detect acute poisoning and single-dose administration if other matrices are unavailable or to provide complementary information for other matrices.